Out-of-Java Students’ Perceptions of Self-Efficacy in English-Speaking Skills - Imelda Woa Wene; Martinus Mersi Vantaosen (SALEE: Study of Applied Linguistics and English Education, 2023)
This study investigates out-of-Java students’ perceptions of their self-efficacy in English-speaking skills. To figure out their perceptions, the researchers formulated two research questions: (1) To what extent do out-of-Java students’ educational backgrounds impact their perceptions of self-efficacy in English speaking skills? (2) How do students cope with the challenges of speaking English? Participants in this study were the third-semester students from English Language Education Study Program. Written reflections and semi-structured interviews were chosen as the primary data collection methods. In analyzing the data, Thematic Analysis was employed in this study. The researchers described the participants’ self-reflections and transcribed their interviews. This study revealed two important results. First, there was an influence of participants' educational backgrounds on their perception of self-efficacy in English-speaking skills. Second, the participants had their strategies in overcoming the difficulties that they experienced in speaking. The results of the study showed that out-of-Java students have high self-efficacy beliefs which increase with their time at university and can improve their English-speaking skills by applying some learning strategies.